The effect of learning process according to multiple intelligences theory on 7th grade students' success and retention level in mathematics [Çoklu zekâ kurami ile öǧretimin 7.sinif öǧrencilerinin matematik başarilarina ve kalicilik düzeylerine etkisi] - (:unkn) unknown (My University, 2011)
The purpose of this study is to research and find out whether the multiple intelligences theory convenient instructions in Grade 7 Mathematics lessons have any effect on the students' mathematical success and retention level. For this purpose, the research was conducted in two 7th grade classes which have 65 students in the Anatolian side of Istanbul. The researchers used one experimental group and one control group. At the beginning of the study, the experimental and control groups were given preliminary test. While the "Symmetry, Coordination of a Point on a Plane, Line Graphics" units were taught using the traditional methods in the control group, Multiple Intelligences Theory based lesson plans were used in the experimental group. The preliminary test was used again as a post test and a retention test. Afterwards, comparisons were made to determine whether the instruction where lesson plans based on Multiple Intelligences Theory are used resulted in a difference between the mathematical success and retention level of these two groups.
Keywords: Coordinate symmetry and line graphics; Mathematics teach; Multiple intelligence theory